Agronomic traits and growing cattle performance for whole-plant corn and forage and grain sorghum silages - Dalke, B.S.; Sonon, R.N. Jr.; Holthaus, D.L.; Pfaff, L.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Agronomic and cattle performance traits were measured for the following silages produced in 1992: irrigated Pioneer 3377 corn, ensiled with or without Biotal® silage inoculant; DeKalb 42Y grain sorghum; and Cargill 200F, Pioneer 947, DeKalb FS-5 and FS-25E, and Northrup King (NK) 300 forage sorghums. All sorghums were grown under dryland conditions. The irrigated corn had the highest whole-plant dry matter (DM) and grain yields, and NK 300 and DeKalb FS-5 had the highest whole-plant DM yields among the sorghums. NK 300 also had the highest grain yield among the sorghums; DeKalb FS-5 and FS-25E had the lowest. Steers fed the irrigated corn silages had the fastest and most efficient gains, and the late-season forage sorghum, DeKalb FS-25E, produced the slowest and least efficient gains. Inoculating the corn silage increased DM recovery, fermentation efficiency, and steer gain per ton of crop ensiled.
Keywords: Beef; Silage; Corn; Sorghum; Growing cattle